Case Report on the Efficacy of Transnasal Sphenopalatine Ganglion Block for the Treatment of Severe Post-Dural Puncture Headache after Failed Subarachnoid Block - Indriani, Ratri Dwi; Nofiansyah, Rian; Kriswidyatomo, Prihatma (Journal of Medicine and Health Technology, 2024)
This paper presents a case report on the management of post-dural puncture headache (PDPH) after failed subarachnoid block anesthesia through trans-nasal sphenopalatine ganglion block (SPGB). PDPH, a distressing complication following procedures like lumbar punctures, can persist despite conservative management and usually happen in multiple or single attempts at successful subarachnoid injections. For a long period, the treatment for severe PDPH was an epidural blood patch. SPGB, targeting the sphenopalatine ganglion (SPG) involved in cranial pain transmission, has emerged as a promising intervention. The case involves a patient experiencing severe PDPH after failed subarachnoid block anesthesia. Although SPGB initially brought relief, a recurrence of headaches followed, highlighting the need for further optimization. The case shows that SPGB could be used as an extra treatment for PDPH that doesn't seem to be working, but more research is needed to find out how well it works in the long term and what the best technique is. The abstract emphasizes the importance of ongoing monitoring and intervention in managing PDPH, offering insights into the challenges and prospects of SPGB in clinical practice.